Peran Matematika dalam Pendidikan STEM: Tinjauan Literatur Sistematis tentang Integrasi Kurikulum dan Pendekatan Pedagogis - Lestari, Dewi Puji; Kamariah; Thana, Paskha Marini (Universitas Dr. Soetomo, 2025)
Abstract STEM (Science, Technology, Engineering, and Mathematics) education is increasingly becoming a major fokus in education, with the goal of equipping students with 21st-century skills. Mathematics serves as a foundation in STEM, supporting conceptual understanding in science and engineering. However, the integration of mathematics into the STEM curriculum remains a challenge, such as teacher readiness, curriculum flexibility, and the availability of supporting media and technology. This Systematic Literature Review (SLR) aims to examine the latest developments and future directions of STEM education with a fokus on curriculum integration and pedagogical approaches involving mathematics. This study uses the PRISMA approach, selecting 48 articles from the Scopus database that are relevant to this topic. The results show that manipulative tools (concrete and virtual), interdisciplinary approaches, and educational technology play a significant role in the successful integration of mathematics into STEM. The main contribution of this study is to provide a thematic map of trends, approaches, and challenges in integrating mathematics, as well as suggesting directions for further research to develop adaptive and collaborative STEM learning models. Keywords: Mathematics Integration, Pedagogical Approach, STEM Education. Abstrak Pendidikan STEM (Science, Technology, Engineering, and Mathematics) semakin menjadi fokus utama dalam dunia pendidikan, dengan tujuan membekali siswa dengan keterampilan abad ke-21. Matematika berperan sebagai fondasi dalam STEM, mendukung pemahaman konsep dalam bidang sains dan teknik. Namun, integrasi matematika dalam kurikulum STEM masih menjadi tantangan, seperti kesiapan guru, fleksibilitas kurikulum, serta ketersediaan media dan teknologi pendukung. Kajian Sistematis Literatur (SLR) ini bertujuan untuk menelaah perkembangan terbaru dan arah masa depan pendidikan STEM dengan fokus pada integrasi kurikulum dan pendekatan pedagogis yang melibatkan matematika. Penelitian ini menggunakan pendekatan PRISMA, dengan memilih 48 artikel dari database Scopus yang relevan dengan topik ini. Hasil menunjukan bahwa alat bantu manipulatif (konkret dan virtual), pendekatan interdisipliner, serta teknologi pendidikan memainkan peran penting dalam keberhasilan integrasi matematika dalam STEM. Kontribusi utama penelitian ini adalah memberikan peta tematik terkait tren, pendekatan dan tantangan dalam integrasikan matematika, serta menyarankan arah fokus penelitian selanjutnya untuk mengembangkan model pembelajaran STEM yang adaptif dan kolaboratif. Kata Kunci: Integrasi matematika, Pendekatan Pedagogis, Pendidikan STEM